Investigating Past, Present, and Future Trends on Interface Between Marine and Medical Research and Development: A Bibliometric Review - Mehdi Zamani; Tetyana Melnychuk; Anton Eisenhauer; Ralph Gäbler; Carsten Schultz (Marine Drugs)
The convergence of marine sciences and medical studies has the potential for substantial advances in healthcare. This study uses bibliometric and topic modeling studies to map the progression of research themes from 2000 to 2023, with an emphasis on the interdisciplinary subject of marine and medical sciences. Building on the global publication output at the interface between marine and medical sciences and using the Hierarchical Dirichlet Process, we discovered dominating research topics during three periods, emphasizing shifts in research focus and development trends. Our data show a significant rise in publication output, indicating a growing interest in using marine bioresources for medical applications. The paper identifies two main areas of active research, “natural product biochemistry” and “trace substance and genetics”, both with great therapeutic potential. We used social network analysis to map the collaborative networks and identify the prominent scholars and institutions driving this research and development progress. Our study indicates important paths for research policy and R&D management operating at the crossroads of healthcare innovation and marine sciences. It also underscores the significance of quantitative foresight methods and interdisciplinary teams in identifying and interpreting future scientific convergences and breakthroughs.